Vocational High School Student Problems: Investigating School Climate and Career Decision-Making Difficulty - Kadiyono, Anissa Lestari; Utami, Shaufika Virisya (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Implementing the Independent Curriculum launched by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia seeks to strengthen the quality of Indonesian education and prepare students to learn the material needed so that the world of work can directly absorb it. Vocational High School (Sekolah Menengah Kejuruan/ SMK) is a secondary school that prepares students to be ready for work. Vocational students need to prepare provisions for the world of work. They must be able to make career decisions in line with the stage of career development, which is the exploration stage, to have a more directed career. This study examined the difficulties of career decision-making in vocational students and the role of school climate that will influence students' career decisions. The study was conducted on several vocational schools in Pangandaran Regency, one of the West Java areas with a high open unemployment rate. The respondents were class XII students with a sample of 180 people. The theoretical concepts used in this study are the School Climate (NSCC, 2015) and the Career Decision-Making Difficulties (Gati et al., 1996). The research design used is a non-experimental approach using linear regression analysis methods. The data collection technique is through online and written questionnaires with stratified and cluster sampling techniques. The results showed a positively significant influence of the school climate on the difficulty of making career decisions by 15.2%. That is, the more positive the perspective of grade 12 Vocational High School students on the school climate, the lower the level of difficulty in making career decisions, and vice versa.